Biofuel supply chain risk mitigation strategy framework: Expert interview based approach - Tedy Wachyudi; Arief Daryanto; Machfud Machfud; Yandra Arkeman (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: The purpose of this case study is to develop and framework supply chain characteristics and risk mitigation strategies in the context of biodiesel downstream supply chain. Design/methodology/approach: This study employs an expert interview-based approach as a qualitative approach with a multi-perspectives view. Findings: There are vary strategies among perspectives, such as perspectives of organization and business types, stakeholder types, times and methods. These also shows that business strategy of collaborative, coordinative, and cooperative arise as alternative strategies for each perspective and each level of stakeholder. Those business strategies may apply in a vary operation strategies which linking through an energy security framework element as company's competitive priorities. Research limitations/implications: The research scope includes only a certain area of the country's territory and the target company's supply chain areas of activity. The research method includes only internal stakeholders and experts as respondents and data sources. The level of analysis was only at corporate level in the corporate case study context. The research also targets only a downstream activities of biodiesel supply chain context. The interview-based approach as a qualitative approach faces some subjectivity challenges among respondents. Practical implications: The research result provides some positive implications for business practice, includes how to minimize the impact of supply chain risk on company's business activities and performance, how supply chain experts and practitioners used risk mitigation practices, how to formulate strategic plans to minimize the impact of supply chain risk and enhance the effectivity and sustainability of the supply chain activities. Social implications: The implication for business practice was that company's leaders implemented supply chain risk mitigation strategies that provide positive impacts on the more valuable relationship among supply chain actors and stakeholders. Originality/value: The first, is an activities areas and operation schemes-based of biodiesel supply chain point of view. The second, is a multi-perspectives-based biodiesel supply chain characteristics framework. The third, is an energy security framework-based biodiesel risk mitigation strategies framework.
Keywords: 650; supply chain; risk mitigation strtaegy; biofuel; expert interview based approach